Cross-cultural professional experiences of female expatriates: Finding success through agility, resilience, and essential relationships. Issue 4 (17th October 2019) - France, Tami; Booysen, Lize; Baron, Carol
Abstract : Purpose: In this world of global interconnectedness, women continue to develop cross-cultural careers and their experiences impact global scholarship and practice. The purpose of this paper is to explore the relationships, resources and characteristics that support female expatriate success, with specific focus on the role of mentor/coach relationships. The sample included 102 women from the USA, Canada, Australia and the UK working or formerly working in Mainland China, Hong Kong, Macau or Taiwan. Design/methodology/approach: This three phase sequential mixed-methods exploratory research study included 10 one-on-one semi-structured interviews, 102 survey respondents and 3 facilitated focus groups attended by nine professional women. Findings: This research offers evidence that resiliency-based characteristics must be cultivated and developed to support expatriate cross-cultural success. These characteristics can be cultivated through relying on multiple relationships, such as mentors, coaches, host country liaisons, expatriate colleagues, friends and family as well as by supporting and mentoring others. These characteristics can also be developed through specific cultural experiences, knowledge and skill building resources, as well as developing an informed view of self and identity clarity through reflective activities. Originality/value: Based on the overall findings, a cross-cultural professional success model was designed and implications for scholarship, organizational effectiveness and cross-cultural leadership practice are presented.